Using the cognitive interview to recall real‐world emotionally stressful experiences: Road accidents. Issue 4 (13th April 2021) - Dodier, Olivier; Ginet, Magali; Teissedre, Frédérique; Verkampt, Fanny; Fisher, Ronald P.
Summary: This study examined the relevance of the cognitive interview (CI) for the recall of a road accident by actual victims, depending on the level of stress experienced at the time of the event. Fifty‐six victims (or witnesses) were interviewed, either with a CI or control interview, after completing a series of questionnaires including measures of their stress level during the accident. Participants who reported a high level of stress recalled more central details than those with a low level. In addition, participants interviewed with the CI recalled more details than those interviewed with a control interview, regardless of the level of stress experienced during the accident. This experiment confirms the CI's relevance in a stressful context, and after an extended period of time. Practical implications for interviewing victims are discussed.